Brain Reorganization and Neural Plasticity in Elite Athletes With Physical Impairments - Nakazawa, K. (Exercise and Sport Sciences Reviews, 2022)
Use-dependent and impairment-specific brain plasticity are hypothesized to interact and enhance neural reorganization in the central nervous system (CNS) of athletes with physical impairments. Paralympic brain studies are helpful in achieving a fundamental understanding of the underlying neural mechanism related to CNS reorganization after physical therapy or athletic training. Information learned from these individuals also provides new insights into sports- and rehabilitation-related neuroscience. Key points: - The human central nervous system (CNS) has the ability to undergo spontaneous reorganization after neurological and physical injuries, such as stroke, spinal cord injury, and limb amputation. - Physical therapy, athletic training, and neuromodulation can induce use-dependent plastic changes in the CNS. - The brains of athletes with physical impairments might have amplified their ability to reorganize because of a combined effect of use-dependent plasticity induced by training and impairment-related neuroplasticity.